Evaluation of suicidal cases: A retrospective 10 years autopsy study - Bork, Turgay; Tokdemir, Mehmet; Türkoglu, Abdurrahım; Batbaş, Muhammet (My University, 2021)
Suicide is a complex process that starts with suicidal thoughts and moves on to planning of suicide and finally suicidal activity. In the present study, we aimed to evaluate the sociodemographic and clinical characteristics of suicide cases and to discuss it the light at literature. In the present study, 356 autopsied suicide cases were retrospectively reviewed. Of a total of 2686 deaths 356 (13.25%) were reported as suicide. The data were obtained from hospital records and files of judicial investigations. Of these cases, 242 (67.9%) were males, the mean age was 36±18.65 years. 132 cases (37.1%) were married. Hanging ranked first with 180 cases (50.6%) among suicide methods, the 15 to 24 years age group ranked first with 108 cases (30.3%). The most common cause of predisposing factors was depression with 107 cases (30.1%). 288 cases (80.9%) occurred in the city centers. The most suicides occurred at home with 157 cases (44.1%). When the suicide cases were evaluated by occupation, 65 (18.3%) were unemployed. Considering the fact that suicide is an important public health concern affecting particularly individuals in the 15 to 34 years age group which is defined as the productive age group, psychological support must be provided to these individuals at the workplaces and dedicated health centers to be established for this purpose.
Keywords: Suicide; autopsy; Forensic medicine